Peningkatan Literasi Siswa Melalui Media Visual Pojok Cerdas (mading) dan Poster Literasi di SDN Gambyok 1 - Ulfiyani, Rizqiyah; Fada , Isti; Angraini , Julia; Azizah, Anita Syayyidatul; Mariana , Tina; Jabbar A , Rajendra Ahmad; Silviana , Ika (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to develop elementary school students literacy media through the use of visual media based on Pojok Cerdas, in the form of bulletin boards and literacy posters, at SDN Gambyok 1. The research utilized a Participatory Action Research (PAR) method, involving active participation of teachers and students in each research phase: planning, action, observation, and reflection. The subjects of the study were lower-grade students and teachers at SDN Gambyok 1, with data collected through observation, interviews, and documentation. The findings reveal that the developed visual media effectively enhances reading interest, information appeal, and student engagement in literacy activities. Literacy posters and bulletin boards play a significant role as educational and attractive tools for delivering information, while also supporting thematic learning aligned with the characteristics of elementary school-aged children. The study recommends the use of similar visual media as an alternative strategy to improve literacy culture in elementary schools, particularly those with limited library facilities